O048 Help seeking behaviours of Australian adults with insomnia in a community sample. (9th November 2022) - Haycock, J; Lack, L; Hoon, E; Sweetman, A; Appleton, S; Reynolds, A; Gill, T; Adams, R; Lovato, N
Abstract: Introduction: Chronic insomnia negatively impacts quality of life for millions of Australians. Most people with insomnia do not receive the recommended treatment Cognitive Behavioural Therapy for insomnia (CBTi), and many are prescribed sedative-hypnotic medications. This study aims to better understand the help seeking behaviours of people with insomnia, and to identify barriers to treatment and improve access to evidence-based care. Methods: A total of 2044 people in a community sample (Age M = 46.6, SD = 17.3, 51.3% Female) completed the 2019 Sleep Health Foundation Insomnia Survey which included questions on sleeping difficulties, daytime impairment and help seeking behaviours. Chronic insomnia was identified using the ICSD-3 diagnostic criteria. Results: Preliminary analysis shows 37% of participants with chronic insomnia (N=303) discussed sleep with their GP in the past year. The most common help seeking behaviours for participants with insomnia are strict sleep habits (50%), adjusting time in bed (47%), relaxation (40%), alcohol (39%), and meditation (37%). Participants with undiagnosed insomnia (N=275) are much less likely to engage in help seeking behaviours than those with a diagnosis. Most participants who discussed sleep with a psychologist (N=104) reported a diagnosis of depression (77%) or anxiety (80%), rather than insomnia (30%). Discussion: Despite evidence-based guidelines recommending CBTi as the 'first line' treatment for insomnia, in Australia most people manage their insomnia with strict sleep habits or relaxation techniques. These findings highlight the importance of GPs discussing sleep with patients, and having knowledge and access to appropriate treatment and referral pathways for management of insomnia.